Photoperiod and dietary treatment in freshwater modulate the short-term intestinal response to seawater in Atlantic salmon (Salmo salar) - Gaetano, Pasqualina; Duarte, Vilma; Striberny, Anja; Hazlerigg, David; Jørgensen, Even H.; Campinho, Marco A.; Fuentes, Juan (Aquaculture, 2023)
Stimulation and timing of smoltification are essential for successful Atlantic salmon (Salmo salar) aquaculture. This study investigated intestinal responses during dietary and photoperiod manipulation in freshwater (FW) and after a subsequent seven days residence in seawater (SW). “Small” and “large” Atlantic salmon parr (∼40 g and ∼ 130 g respectively) were treated in FW for 12 weeks and thereafter transferred to SW for seven days. During the FW phase, fish underwent two different light conditions, 24 L:0D – 24 L (“LL-LL” groups) and 7 L:17D – 24 L (“SP-LL” groups) or fed with either regular feed (“LL-LL C" and “SP-LL C" groups) or feed enriched with a salt mix plus free tryptophan (“LL-LL + diet” and “SP-LL + diet” groups). We analyzed Na+/K+-ATPase (NKA) activity, tissue bioelectrical properties in Ussing chambers, and intestinal fluid composition. The NKA activity showed minor variations in relation to fish size, treatments, or intestinal region (anterior or posterior). Photoperiod modulated epithelial bioelectrical properties (Isc and Rt) of the anterior and posterior intestine, particularly transepithelial resistance (Rt). Pharmacological experiments, targeting apical Na+/K+/2Cl− (NKCC2) and Na+/Cl− (NCC) co-transporters revealed intestinal region- and water salinity-dependent effects. In addition, stimulation of the intracellular cAMP with forskolin and IBMX showed intestinal region-, water salinity, and treatment-dependence responses with clear functional specialization of the anterior and posterior intestine. The intestinal fluid composition reflected the ability to process ingested SW and showed little variation in large fish. In summary, our data suggest a better pre-adaptation of the intestine during light-stimulated smoltification (SP-LL groups), and the combination of light and diet might give, in an industrial aquaculture setting, an advantage to smaller, but not larger smolts. Intestinal fluid composition in small fish can be used as an index of intestinal function and may act as a long-term performance proxy in SW Atlantic salmon. •Functional specialization of anterior and posterior intestine in Atlantic salmon smolts.•Size-dependent response to photoperiod and diet in Atlantic salmon.•Photoperiod and diet represent a benefit for SW adaptation of small smolts.•Intestinal fluid analysis provides a valuable index for long-term seawater performance.